Design of robust adaptive fuzzy control for uncertain bilateral teleoperation systems based on backstepping approach. Issue 7 (1st March 2023) - Bouteraa, Yassine; Alattas, Khalid A.; Peng, Tongrui; Fekih, Afef; Rahmani, Reza; Mobayen, Saleh
Abstract: In this study, a novel method based on a robust adaptive fuzzy control approach is developed for nonlinear teleoperation systems. Its main objectives are to ensure system stability and properly mitigating parametric uncertainties stemming from external disturbances and un‐modelled dynamics. For the communication channel, instead of the direct transmission of environmental torque signals, the approximated environmental parameters by the fuzzy system are transmitted to the master side for the prediction of environmental torque, thus successfully avoiding the transmission of the power signals in the delayed communication channel and solving the passivity problem in the teleoperation system. Besides, a trajectory generator is employed in the master side, whereas a trajectory smoothing is provided in the slave side. Theoretically, it was proven that both position tracking and force feedback problems are attained. Using Lyapunov stability analysis, this work illustrates that the robust adaptive fuzzy controller based on the backstepping approach guarantees the system's asymptotic stability. Simulation results confirm the efficiency of the suggested control technique in achieving the stability and tracking objectives of the uncertain nonlinear teleoperation system. Abstract : In this study, a novel backstepping‐based method based on a robust adaptive fuzzy control approach for nonlinear teleoperation systems has been developed to overcome the parametric uncertainties (including external disturbances and un‐modelled dynamics). For the communication channel, instead of the direct transmission of environmental torque signals, the fuzzy approximate environmental parameters are transmitted to the master side for prediction of environmental torque, which successfully avoids the transmission of the power signals in the delayed communication channel and it solves the passivity problem in the teleoperation system.